Preoperative Comorbidities and Postoperative Complications Do Not Influence Patient-Reported Satisfaction Following Humeral Head Resurfacing: Mid- to Long-term Follow-up of 106 Patients. (February 2019) - Beck, Andrea; Lee, Hannah; Fourman, Mitchell; Giugale, Juan; Zlotnicki, Jason; Rodosky, Mark; Lin, Albert
Background: Humeral head resurfacing (HHR) has emerged as an alternative treatment for glenohumeral osteoarthritis. We investigated the outcomes of HHR using validated patient-reported outcome (PRO) measures. Methods: A retrospective review was performed on 213 patients who underwent HHR. A PRO follow-up was performed by administering a questionnaire including the American Shoulder and Elbow Society (ASES) score, Brophy activity survey, short form of the Disabilities of the Arm, Shoulder and Hand (quickDASH) survey, and general shoulder function. PRO scores were stratified by comorbidities and complications. Results: Survey responses were received from 106 patients (51%), with a mean follow-up of 5.6 ± 1.8 years (range: 9 months to 6.1 years). Preoperative comorbidities were associated with significantly higher quickDASH scores. Postoperative complications were associated with significantly higher rates of current pain, higher visual analog scale scores, night pain, lower subjective shoulder values, and lower ASES pain and total scores. No differences in patient satisfaction were identified between the cohorts with and without preoperative comorbidities and between the cohorts with and without postoperative complications. Conclusion: In our cross-sectional analysis of mid- to long-term outcomes following HHR, preoperative comorbidities, or postoperative complications had no impact on patient-perceived postoperative satisfaction or most PROs. HHR is clinically viable in a wide variety of patients. Future work is necessary to compare the efficacy of HHR compared with more traditional total shoulder arthroplasty and stemmed hemiarthroplasty regarding long-term outcomes and appropriate indications.